Proceedings of the IGSHPA Research Track 2018 2018
DOI: 10.22488/okstate.18.000014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal performance assessment of a dual source heat pump system for heating, cooling and domestic hot water production

Abstract: In order to contribute to a global CO 2 emissions reduction in 2020, the increase in the use of highly efficient heat pumps for heating, cooling and domestic hot water production in buildings is very recommendable. In this direction, Ground Source Heat Pump (GSHP) systems are generally recognized as one of the most energy-efficient compared to air source heat pump systems. However, this strongly depends on the temperature evolution of the air and the ground during the year, which also depends on the geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…A novel "plug-and-play" DSHP, capable of working in eleven operating modes, was designed and modeled in TRNSYS, which is described by Corberán et al in the following study [25]. Another work, by Cazorla-Marín et al, in which the integrated DSHP system was adapted to three different locations in Spain (Valencia, Madrid, Bilbao), analyzed the percentage of operation of the DSHP under each of the selected working modes [26]. An extension to this study, where an office building with the DSHP unit is simulated for three different European cities with representative climates-Strasbourg (average climate), Athens (warmer climate), and Stockholm (colder climate)-concluded that in warmer climates the use of DSHP is not as profitable as in cold climates, as the air is used to satisfy only 4% of the thermal energy demand [27].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A novel "plug-and-play" DSHP, capable of working in eleven operating modes, was designed and modeled in TRNSYS, which is described by Corberán et al in the following study [25]. Another work, by Cazorla-Marín et al, in which the integrated DSHP system was adapted to three different locations in Spain (Valencia, Madrid, Bilbao), analyzed the percentage of operation of the DSHP under each of the selected working modes [26]. An extension to this study, where an office building with the DSHP unit is simulated for three different European cities with representative climates-Strasbourg (average climate), Athens (warmer climate), and Stockholm (colder climate)-concluded that in warmer climates the use of DSHP is not as profitable as in cold climates, as the air is used to satisfy only 4% of the thermal energy demand [27].…”
Section: Introductionmentioning
confidence: 99%
“…Another work, by Cazorla-Marín et al, in which the integrated DSHP system was adapted to three different locations in Spain (Valencia, Madrid, Bilbao), analyzed the percentage of operation of the DSHP under each of the selected working modes [26]. An extension to this study, where an office building with the DSHP unit is simulated for three different European cities with representative climates-Strasbourg (average climate), Athens (warmer climate), and Stockholm (colder climate)-concluded that in warmer climates the use of DSHP is not as profitable as in cold climates, as the air is used to satisfy only 4% of the thermal energy demand [27]. Another work by Cazorla-Marín et al consisted of the implementation of a coaxial borehole heat exchanger TRNSYS type into the previously developed DSHP model, which allowed for both short-and mid-term simulations [28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations